Development of a neutron beam monitor with a thin plastic scintillator for nuclear data measurement using spallation neutron source. Issue 12 (2nd December 2022) - Nakano, Hideto; Katabuchi, Tatsuya; Rovira, Gerard; Kodama, Yu; Terada, Kazushi; Kimura, Atsushi; Nakamura, Shoji; Endo, Shunshuke
ABSTRACT: A neutron monitoring detection system was developed for neutron capture cross-section measurement using a spallation neutron source. A combination of a plastic scintillator and a thin 6 LiF foil was adopted for the detector. The detector system was tested to study the feasibility of the system. Neutron irradiation experiments were conducted with the Accurate Neutron-Nucleus Reaction Measurement Instrument in the Materials and Life Science facility of the Japan Proton Accelerator Research Complex. A neutron time-of-flight spectrum was successfully measured without significant count loss or detector paralysis. GRAPHICAL ABSTRACT: uf0001